The experience of unmarried mothers raising their children in residential facilities: a phenomenological qualitative study - Sungjae Kim; Kyung-Sook Bang; Yeseul Jeong; Gumhee Lee; Da-Ae Shin; Misook Kim (BMC, 2022)
Abstract Background Birth outside of marriage has been gradually increasing in Korea. However, social perception of unmarried mothers is still negative, and a number of them are not accepted by their family. Therefore, the Korean government has implemented a policy to provide financial aid and communal residence to unmarried mothers who cannot raise children with their family, or afford residence. Unmarried young mothers who rely on this government policy have low economic independence and social adaptation skills. Additionally, they have a high chance of encountering numerous challenges in raising children due to their living conditions in residential facilities and social prejudice. This study was conducted to gain an in-depth understanding of the lived experience of unmarried mothers raising children in residential facilities. Methods Data were collected through in-depth interviews with nine unmarried mothers living in residential facilities with their children. An interpretative phenomenological analysis was conducted to analyze the data. Results The findings revealed that unmarried mothers struggled with various difficulties given the limitations of living in the facility, but attempted to navigate their uncertain future with the determination to be good mothers. Three main themes and eight sub-themes emerged: (1) adaptation to the identity of "unmarried mother", (2) willingly undertaking the heavy burden of childrearing, (3) indispensable but insufficient supports from facilities. Participants had childrearing responsibilities, and tried to be good mothers for their children while struggling to adapt to their new identities. However, their self-doubt as a "good mother" and the absence of the child's father made them feel sorry for their child. Their daily experiences raising children and simultaneously preparing for their own independence were exhausting. The supports from the facilities were helpful but unsatisfactory and led to various psychosocial difficulties such as anxiety, depression, fear, guilty, and anger in unmarried mothers. Conclusions Besides information and resources for parenting and independence, active approaches are needed to improve the psychological stability of unmarried mothers raising their children in facilities, and sustain a long-term socioeconomic support system. Thoughtful services tailored to mothers and children are also needed, instead of standardized services.